MENGUAK REALITAS PRAKTIK SEDEKAH BUMI DI DESA CIASMARA KECAMATAN PAMIJAHAN KABUPATEN BOGOR - Supriatna, Raden Atang; Nugraha, Yogaprasta Adi (Fakultas Ilmu Budaya, Universitas Mulawarman, 2020)
Agriculture is one of the important sectors that contribute to Indonesian national income. However, agricultural development currently has a tendency to increase productivity it impacts on the agricultural system which tends to make agriculture as